The application of hotel strategies based on factor analysis to improve the number of events at The Trans Resort Bali - I Putu Yana Arya Kusuma; I Nyoman Rajin Aryana; I Gusti Agung Mas Krisna Komala Sari (Politeknik Negeri Bali, 2021)
This research was conducted at The Trans Resort Bali, a 5-stars hotel located in Seminyak, Badung, Bali. The purposes of this research was to found out the factors affected the customers’ decision to hold an event, found out the most dominant factor and found out the strategies should be applied to maintain the factors and improve the number of events at The Trans Resort Bali. The sample was 74 respondents using cluster sampling technique. The steps taken in data processing was looking for the results of the validity test and the reliability test of the data, after that factor analysis consist of 6 steps. Based on the results of the research, there were 4 factors affecting the customers’ decision to hold events at The Trans Resort Bali. These factors are facility and environmental factors with a percentage of the variance of 46.193%, service quality factors with a percentage of the variance of 5.928%, information factors with a percentage of the variance of 5.503% and promotion factors with a percentage of the variance of 5.294%. The value of the accuracy of the model is 60% with a residual of 40%. From the 4 factors were found the most dominant factor which is facilities and environment factors consist of 4 variables, namely (1) Ballroom & Boardroom that is luxurious and spacious, (2) attractive and luxurious venue design, (3) strategic hotel location and (4) complete meeting and event facilities.